PEMANFAATAN DAN OPTIMASI TAKARAN BUAH BOGEM (Sonneratia caseolaris) SEBAGAI BAHAN BAKU PEMBUATAN NATA - L. Sugiarti; Susie Amilah (FMIPA : Universitas PGRI Adi Buana, 2013)
This study aims to eksplore utilization and optimal dose of fruit punch as raw materials for nata production. This work was conducted using completely randomized design consisting of 5 treatments (333, 250, 200, 170 dan 140 g/l) with 4 replication. Each of dose fruit punch added on basal medium consisting of 100 g/l gula, 5 g/l urea and 10% starter culture of A.xylinum. Results showed dose of fruit punch have significant (P<0.05) effect on yield, firmness, carbon and nitrogen consumption and sensory characteristic. Highest yield (42,14±0,20 g/l), firmnesss (4,24±0.16 g/l), carbon (2,01±0,17%) and nitrogen (0,33±0,12%) consumption have obtained from fruit punch 333 g / l In the medium dose of fruit punch in 333 g / l (2.01 ± 0.17%). Most prefered color of nata (3,75±0,06) was obtained from 333 g/l, neverless most prefered both of taste (3,63±0,04) and aroma (3,37±0,02) were obtained from 140 g/l fruit punch. This study take conclusion that fruit punch can utilize as raw material for nata with optimum dose 333 g/l. Keywords: Sonneratia caseolaris, nata, carbon and nitrogen consumption, production, firmness, organoleptic.